การวิเคราะห์ตำแหน่งตราสินค้าของผลิตภัณฑ์กระดาษเช็ดหน้า โดยใช้เทคนิคการแบ่งสเกลแบบหลายมิติ - บุนนาค, ชื่นสุมล; อารีย์, บุษราภรณ์ (Journal of Business, Innovation and Sustainability (JBIS), 2016)
งานวิจัยนี้มีวัตถุประสงค์เพื่อแสดงการวิเคราะห์ตำแหน่งตราสินค้าของผลิตภัณฑ์กระดาษเช็ดหน้าทั้งที่เป็นสินค้าเฮ้าส์แบรนด์และสินค้าแบรนด์ ทั้ง 3 ระดับ ได้แก่ระดับที่ 1 คือ “Good” ระดับที่ 2 คือ “Better” และระดับที่ 3 คือ ระดับ “Best” ระหว่างห้างบิ๊กซีซูเปอร์เซ็นเตอร์และห้างเทสโก้โลตัสในเขตกรุงเทพมหานคร รวมถึงศึกษาพฤติกรรมผู้บริโภคที่มีต่อการตัดสินใจซื้อผลิตภัณฑ์กระดาษเช็ดหน้าทั้งที่เป็นตราสินค้าเฮ้าส์แบรนด์และสินค้าแบรนด์ในเขตกรุงเทพมหานคร จำนวน 60 คน โดยใช้แบบสอบถาม (Questionnaire) ให้ผู้ตอบแบบสอบถามได้ทดลองสัมผัสสินค้า (Blind Test) เพื่อให้ได้ข้อมูลเกี่ยวกับความพึงพอใจในผลิตภัณฑ์กระดาษเช็ดหน้าทั้งที่เป็นสินค้าเฮ้าส์แบรนด์และสินค้าแบรนด์ทั้ง 3 ระดับ สถิติที่ใช้ในการวิเคราะห์ข้อมูล ได้แก่เทคนิคการแบ่งสเกลแบบหลายมิติ (Multidimensional Scaling Technique) หรือ MDS เพื่อแสดงภาพการรับรู้ตำแหน่งผลิตภัณฑ์ของผู้บริโภคที่มีต่อผลิตภัณฑ์กระดาษเช็ดหน้าทั้งที่เป็นสินค้าเฮาส์แบรนด์และสินค้าแบรนด์ เมื่อจำแนกตาม 4 องค์ประกอบ ได้แก่ 1.คุณประโยชน์หลัก 2.รูปลักษณ์ผลิตภัณฑ์ 3.คุณภาพของสินค้า 4.ราคา ผลจากการวิจัยพบว่า จากการแสดงภาพการรับรู้ของผู้บริโภค (Perceptual Map) มีความคล้ายคลึงกันในแต่ละระดับสินค้าในแต่ละองค์ประกอบมากกว่า 50% ในทุก 4 องค์ประกอบ The Multidimensional Scaling Technique (MDS) for Analyzing Facial Tissue Brand The objectives of this research are to analyze the facial tissue brand positioning of House Brand and Brand products comparing 3 levels positioning as followings; Level 1 means Good, Level 2 means Better and Level 3 means Best between Big C supercenter and Tesco Lotus in Bangkok including the study of customer behavior which affects to decision making of purchasing facial tissue brand products. The questionnaires, collected with 60 respondents, are employed as research tool and testing customer perception with both of facial tissue brand products and house brand products in blind test. 60 respondents were asked about the satisfaction of facial tissue brand and house brand products of 3 levels by putting their judgments into questionnaires. The statistical analysis of the responses data was used as Multidimensional Scaling Technique or MDS technique to show the positioning of facial tissue brands. The perception of consumers between facial tissue house brand and brand products are classified into 4 factors as follows: 1. The basic benefits 2. Products package 3. The quality of the products 4. Price. The research result showed that the visual perception of consumers (Perceptual Map) were similar in each level and in each of 4 components were similar more than 50% in all components. DOI: http://dx.doi.org/10.14456/becj.2014.20